Life tables of Bactericera cockerelli in solanaceous crops - Panchi, N.; Gamarra, H.; Chicaiza, D.; Carhuapoma, Pablo; Kreuze, Jan F. (2025)
This technical report demonstrates that the development, survival, and reproductive capacity of Bactericera cockerelli are strongly dependent on the interaction between temperature and host plant. While Solanum nigrum acts as an unsuitable host (a potential biological barrier), sweet potato (Ipomoea batatas) and cape gooseberry (Physalis peruviana) allow the psyllid to complete its life cycle under fluctuating temperatures, which has critical implications for integrated pest management at the landscape scale. The study aligns strongly with Crop Protection, Climate-smart Agriculture, and Resilient Agrifood Systems, providing key evidence for managing the potato psyllid under climate change scenarios.